Furmidable foes [large type] - Brown, Rita Mae; Brown, Sneaky Pie, 1982- (Brown, Rita Mae. Mrs. Murphy mystery., 2020)
"Someone's passed their expiration date in this thrilling new mystery in the bestselling Mrs. Murphy series from Rita Mae Brown and her feline co-author Sneaky Pie Brown. Mary Minor "Harry" Harristeen and her pet sleuths uncover a rotten scam to dupe consumers when they discover that substandard produce is being passed off for organic, upmarket groceries. As always, Harry's crime-solving cats Mrs. Murphy and Pewter and Tee Tucker the Corgi share her determination to sniff out the foes among friends, the spoiled among the fresh"--